Using Theory to Explore the Determinants of Medication Adherence; Moving Away from a One-Size-Fits-All Approach - Claire Easthall; Nina Barnett (MDPI AG, 2017)
Non-adherence to prescribed medicines has been described as "a worldwide problem of striking magnitude", diminishing treatment effects and wasting resources. Evidence syntheses report current adherence interventions achieve modest improvements at best, and highlight the poor progress toward the longstanding aim of a gold-standard intervention, tailored to meet individual need. Techniques such as motivational interviewing and health coaching, which aim to facilitate patient-centred care and improve patient resourcefulness, have shown promise in supporting adherence, especially in patients with psychological barriers to medicine-taking, such as illness perceptions and health beliefs. Despite a plethora of research, there is little recognition that the nature and complexity of non-adherence is such that a one-size-fits-all approach to interventions is never likely to suffice. This commentary re-visits the call for adherence interventions to be tailored to meet individual need, by considering what this means for day-to-day practice and how this can be achieved. It provides an update on advances in psychological theory to identify the root cause of an individual's non-adherence to encourage matching of provided adherence support. It also provides a practical perspective by considering exemplars of innovative practice and evaluating the day-to-day practicalities of taking a novel approach.